O EXTRATO METANÓLICO DA RAIZ DE Lonchocarpus cultratus INIBE DIFERENTES PRODUTOS DA RESPOSTA INFLAMATÓRIA DE MACRÓFAGOS - Lima, Lucas Bonatto de Souza (2022)
The scientific research involving vegetal extracts, consists not only in a considerable source of pharmaceutical molecules, but also represents an important tool in the studies of the immunological system and the inflammatory process. It is well known that plants from the Lonchocarpus genus have secondary metabolites with immunomodulatory properties, and the extract from L. cultratus has been studied in previous research, demonstrating an anti-parasite activity. Hence, through cell culture techniques, it is possible to evaluate the influence of vegetal extracts on the inflammatory activity, analyzing the cell’s response due to the stimulation by the secondary metabolites, present in these extracts. This research’s objective was to evaluate the pro-inflammatory and anti-inflammatory effect of the methanolic extract of Lonchocarpus cultratus over macrophages. The cell lines used here were RAW 264.7 macrophages. The concentration of the methanolic extract from the roots of L. cultratus was 175 µg/mL. Evaluation of the inflammatory response was made through quantification of the nitric oxide (NO), dosing of superoxide anion (O2 - ), arginase activity, production of tumoral necrosis factor alfa (TNF-α), production of interleukin 10 (IL-10) and analysis of mitogen activated protein kinase pERK ½ (also known as pERK 44/42) pathway. The extract was able to attenuate the pro-inflammatory response by downregulating the production of NO, O2 - and TNF-α, however it couldn’t increase the production of IL-10 and arginase, components of the anti-inflammatory process, moreover the intracellular production of pERK ½ wasn’t altered significantly.